Pengaruh Edukasi Media Poster Terhadap Pengetahuan Personal Hygiene Siswi Saat Menstruasi Di Pondok Pesantren Assalam Kota Manado - Vivi Sri Utami Gobel; Nelfa Fitria Takahepis; Merry H. Rimporok (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The lack of reproductive health knowledge about personal hygiene during menstruation among young women, obtained from parents and schools, causes the knowledge and behavior of young women about personal hygiene during menstruation to be very lacking. One effort to increase knowledge of adolescent reproductive health is by providing health education using poster media. The aim is to determine the effect of poster media education on female students' knowledge of personal hygiene during menstruation at the Assalam Islamic boarding school, in Manado City. The method used in this research was pre-experimental with a one-group pretest-posttest design approach. The sample taken was 18 subjects using purposive sampling. Data collection uses questionnaire sheets and SAP (Extension Event Unit). The collected data was processed using test. Statistical tests use the McNemar Test with a significance level of ≤ 0.05. The research results obtained a value of p = 0.000 (α ≤ 0.05) so that Ha was accepted, meaning that there was an influence of poster media education on female students' knowledge of personal hygiene during menstruation at the Assalam Islamic Boarding School, Manado City. The conclusion based on the research results is that there is an influence of poster media education on female students' knowledge of personal hygiene during menstruation at the Assalam Islamic Boarding School, Manado City. Suggestions for future researchers can use other media as comparison material so that they can add more information